Corrosion behavior of magnesium and magnesium–hydroxyapatite composite fabricated by friction stir processing in Dulbecco's phosphate buffered saline. (March 2016) - Ahmadkhaniha, D.; Fedel, M.; Heydarzadeh Sohi, M.; Zarei Hanzaki, A.; Deflorian, F.
Highlights: Friction stir processing induced basal texture and refined magnesium structure. Corrosion mechanism of magnesium was changed by friction stir processing. A competition between grain size and texture exists on magnesium corrosion behavior. Hydroxyapatite particles embedded in magnesium changed its corrosion behavior. Abstract: Magnesium–hydroxyapatite composite was fabricated by friction stir processing. The effects of hydroxyapatite particles addition along with structural refinement on the corrosion resistance of the composite were investigated by electrochemical techniques and X-ray diffraction analysis. The results indicate that the achieved grain refinement (18 μm) and the dominated basal texture in friction stir processed (FSPed) magnesium would properly enhance corrosion resistance by more than one order of magnitude after 96 hours of immersion. However, addition of hydroxyapatite particles would weaken the basal texture, thereby deteriorating the corrosion resistance to less than 20% of that of in FSPed Mg.